Medical secrecy in the context of doctor’s obligation and patient’s right: legal analysis - Riabchynska, O.; Stomatov, E.; Anishchenko, M. A.; Filei, Yu. V.; Аніщенко, Михайло Анатолійович (My University, 2022)
The Article points out the existence of certain problems with the regulation of certain aspects of the consolidation and implementation of medical secrecy in Ukraine. Emphasis is placed on the need for legal analysis and proposals for their solution. It also emphasizes the need to develop a comprehensive approach to building public confidence in the system of medical services, which should be based on the establishment of effective state guarantees for the protection of patients’ rights, which includes the institution of medical secrecy. It has been determined to which legal regime information on the state of health of an individual belongs under the current legislation of Ukraine and the official interpretation of the Basic Law by the Constitutional Court of Ukraine.